Os desafios da participação popular no orçamento participativo no município de São GonçaloThe challenges of the popular participation in the participatory budgeting in the municipal district of São Gonçalo - de Melo Barros, Jaqueline (Revista Linhas, 2007)
O objetivo do presente estudo foi analisar como se configurou a participação popular no processo de construção do Orçamento Participativo no município de São Gonçalo, na Região Metropolitana do Estado do Rio de Janeiro. O Orçamento Participativo tem se revelado como um dos instrumentos que contribuem para a construção de uma nova cultura política, a partir da participação da população na implementação e deliberação de políticas públicas. Assim, a participação passa a ser concebida como um meio de exercer o controle social sobre o Estado, onde a sociedade civil é capaz de intervir na elaboração e fiscalização das ações públicas. PALAVRAS-CHAVE: Gestão democrática. Cidadania. Participação Popular. The present study intends to analyze as the popular participation was configured in the process of construction of the Participatory Budgeting in the municipal district of São Gonçalo, in the Metropolitan Area of the State of Rio de Janeiro. Participatory Budgeting has been revealing as one of the instruments that they contribute to the construction of a new political culture, starting from the participation of the population to implement and deliberate public politics. Thus, the participation becomes conceived as a middle of exercising the social control on the State, where the civil society is capable of intervening in the elaboration and checking the public actions. KEYWORDS: Democratic administration. Citizenship. Popular Participation.